Sounding objects : musical instruments, poetry, and art in Renaissance France - Zecher, Carla, 1959- (University of Toronto Press, 2007)
"In Sounding Objects, Carla Zecher studies the representation of musical instruments in French Renaissance poetry and art, arguing that the efficacy of these material objects as literary and pictorial images was derived from their physical characteristics and acoustic properties, as well as from their aesthetic product." "Sounding Objects is concerned with ways in which musical culture provided poets with a rich, nuanced vocabulary for reflecting on their own art and its roles in courtly life, the civic arena, and salon society. Poets not only depicted the world of musical practice but also appropriated it, using musical instruments figuratively to establish their literary identities. Drawing on music treatises and archival sources as well as poems, paintings, and engravings, this study aims to enrich our understanding of the interplay of poetry, music, and art in this period, and highlights the importance of musical materiality to Renaissance culture."--Jacket.